Coordination Analysis of Over Current Protection Using ETAP Software: A Case Study in PT Indocement Tunggal Prakarsa Tarjun, Kotabaru, South Kalimantan - Setiawan, Aditiya; Syahputra, Ramadoni; Chamim, Anna Nur Nazilah; Jeckson, Jeckson (Journal of Electrical Technology UMY, 2019)
PT Indocement Tunggal Prakarsa Tarjun, Tbk Plant 12, is the largest cement company in Kalimantan. The growing industrial world in the field of cement that is very rapidly will significantly affect the speed of the economy. Thus the increase in the field of electricity will be more felt. PT Indocement Tunggal Prakarsa Plant 12, located in South Kalimantan, requires a reliable electrical system, both in terms of its power supply, in terms of backup of installed electrical systems, as well as safeguards that meet the electricity standards. In the short-circuit settlement is not desired, then the protection of the current relays more with proper coordination protection and reliable required. The coordination of the protection of the current relay is more necessary than the others in order to occur short circuit occurs in the field. No widespread damage occurred in its electricity and existing industrial equipment. To maintain the condition of the electric power system in optimum absence, a re-study of the coordination of current relational protection in PT Indocement Tunggal Prakarsa, Tbk Plant 12. This final project will discuss coordination analysis of overcurrent relay protection at PT. Indocement Tunggal Prakarsa, Tbk. In analyzing the coordination of overcurrent protection, then using several methods in a more coordinated way with coordination protection resetting using ETAP software. They are also resetting coordination protection overcurrent relays using manual calculations. After making the comparison, it can be seen as more current relay protection installed in the field. Some do not work well. It is pronounced in the work of existence, which does not match the standard ie, 0.2 - 0.35 seconds from the IEEE.